Ripple effect and regional house prices dynamics in China - Lee, Chi-Chuan; Lee, Chien-Chiang; Chiang, Shu-Hen (International Journal of Strategic Property Management, 2016)
This paper examines the stationarity properties, the long-run equilibrium and the leadlag relationship among the regional house prices in China from December 2000 to July 2013. Unlike traditional unit-root tests, the panel seemingly unrelated regressions augmented Dickey-Fuller (SURADF) unit-root test reveals that the regional house prices in China are a mixture of I(0) and I(1) processes. There is concrete evidence in favor of the hypothesis of a long-run equilibrium relationship among all regions, except for Shanghai region, and supporting the price diffusion or ripple effect among these Chinese cities. Finally, we determine that these regional house prices exhibit uni-directional causalities running from Beijing, Chongqing, and Shenzhen to Guangzhou and Tianjin, respectively.First Publish Online: 14 Dec 2016